Good thoughts, bad thoughts?: investigating the nature of the wandering mind and how to capture It - Steindorf, Lena (2020)
This dissertation aims at painting a balanced picture of the wandering mind’s nature, strengthening an adaptive view of the phenomenon of drifting thoughts. First, negative consequences of drifting thoughts will be contrasted with positive ones, and I further aim to bring both sides of the medal more in line by focusing on thought-regulation processes. Previous insights will then be enriched by new contributions: I will introduce memory as a newly considered domain, which I found to benefit from mind-wandering processes. From a more methodological perspective and within the domains of creativity and problem-solving, I will not only take a look at possible further mind-wandering benefits, but also present a new research paradigm. This paradigm allows for the closer investigation of possibly thought-altering and intrusive effects of thought probes, the most widely applied mind-wandering assessment method. Thought probes ask participants about their current thoughts during a task and might thus modify the mind-wandering experience itself, thereby complicating the search for positive effects of the phenomenon. As such probes further rely on self-reports and thus contain a subjective component, I will finally report a review and validation study of eye-movement measures as objective mind-wandering indicators. Thus, this dissertation presents an investigation of the nature of the wandering mind as well as of subjective and objective thought-assessment methods.